ANALISIS EFEKTIVITAS PERAN PANITIA PEMERIKSAAN TANAH B DALAM UPAYA MENCEGAH SENGKETA PERTANAHAN DALAM PEMBERIAN HAK GUNA USAHA PERKEBUNAN KELAPA SAWIT DI PROVINSI KALIMANTAN BARAT - SIGIT ARIBOWO, SH A.2021131013, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses the analysis of the effectiveness of the role of the Land Investigation Committee B (Committee B) in an effort to prevent land disputes in the provision of leasehold oil palm plantations in West Kalimantan Province. With the aim to reveal how much the role of the Committee and in the provision of leasehold oil palm plantations can prevent disputes over land and reveals the factors that cause the occurrence of land disputes in the provision of leasehold oil palm as well as the efforts taken by the Committee B and to prevent disputes in the granting of land leasehold. Through the approach of empirical legal research is concluded, that the Committee B as one element of land registration in the National Land Agency of the Republic of Indonesia basically have to carry out their duties in accordance with the purpose of the law and applying the principles of good governance, so as to help the Head of National Land Agency Republic of Indonesia/Regional Head of the National Land Agency, in order to establish the provision of leasehold oil palm plantations that can provide legal certainty, while also providing legal protection of the interests of various parties. In carrying out its role Committee B stated quite effective in the execution of his duty to prevent land disputes in the provision of leasehold oil palm plantations, since the inspections soil Committee B was not only looking for the truth formal (procedural) on the physical data and juridical data for leasehold, but also seek substantive truth of the required documents request leasehold attached, by gathering information from the various parties concerned. The factors that could cause land disputes in the provision of leasehold palm oil is the internal factors are not orderly land administration at the National Land Agency both at the central, provincial and district/city and inaccurate and not carefully attendant land registration in the land registry. Besides, it is also influenced by external factors, namely the existence of bad faith of the applicant, not orderly village level land administration/village, the regional divisions that led to the disputed administrative boundaries and overlapping land use due to the different interests in spatial land use. In practice, efforts are being taken by the Committee and to prevent land disputes in the provision of leasehold among others, by delaying the provision of leasehold oil palm plantations to the problems that exist related to the land being requested has been no settlement is accompanied by evidence of completion or can concluded that the application for land use permits have been clean and clear.Keywords : committee b ? land investigation ? land use permit ? oil palm plantation